2015
DOI: 10.1016/j.seizure.2015.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up after epilepsy surgery in infancy and early childhood – A prospective population based observational study

Abstract: This is the first prospective, population based, longitudinal study to show that a favourable seizure outcome is achievable in a majority of infants and young children undergoing resective epilepsy surgery and that the improvements are consistent over time. Many can also stop taking AEDs. The findings emphasise the importance of early referral to epilepsy surgery evaluation in cases of medically intractable epilepsy in infants and young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 26 publications
3
41
1
Order By: Relevance
“…28 Alternative therapeutic strategies to pharmacology may be advised in the early stages, as shown recently by Reinholdson et al, 29 who through a prospective, population-based, longitudinal study, described the outcomes of 47 children having undergone ablative surgery when younger than 4 years of age. 28 Alternative therapeutic strategies to pharmacology may be advised in the early stages, as shown recently by Reinholdson et al, 29 who through a prospective, population-based, longitudinal study, described the outcomes of 47 children having undergone ablative surgery when younger than 4 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Alternative therapeutic strategies to pharmacology may be advised in the early stages, as shown recently by Reinholdson et al, 29 who through a prospective, population-based, longitudinal study, described the outcomes of 47 children having undergone ablative surgery when younger than 4 years of age. 28 Alternative therapeutic strategies to pharmacology may be advised in the early stages, as shown recently by Reinholdson et al, 29 who through a prospective, population-based, longitudinal study, described the outcomes of 47 children having undergone ablative surgery when younger than 4 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34] Previous studies, mostly retrospective, revealed that children with drug-resistant focal epilepsy score lower on IQ tests, and in particular regarding to memory. [26][27][28][29][30][31][32][33][34] Previous studies, mostly retrospective, revealed that children with drug-resistant focal epilepsy score lower on IQ tests, and in particular regarding to memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most surgical series report outcomes with respect to seizure control, but the deficits incurred are generally not completely documented, a consideration particularly relevant for the subset of patients in whom the EZ is close to or involves the EC. Table presents the possible outcome categories based on seizure freedom and deficits incurred.…”
Section: Introductionmentioning
confidence: 99%
“…Although some centers are conservative and favor a smaller albeit "incomplete" resection to preserve eloquent function, [2][3][4] "complete" resections of the EZ are believed to achieve higher rates of seizure freedom and can prompt aggressive resection of EC. 5 Most surgical series report outcomes with respect to seizure control, but the deficits incurred are generally not completely documented, [6][7][8][9][10][11][12][13][14][15][16] a consideration particularly relevant for the subset of patients in whom the EZ is close to or involves the EC. Table 1 presents the possible outcome categories based on seizure freedom and deficits incurred.…”
Section: Introductionmentioning
confidence: 99%